2010
DOI: 10.3109/09637486.2010.495710
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-use micronutrient fortification: lessons learned in implementing a preschool-based pilot trial in South Africa

Abstract: This current pilot trial assessed the feasibility of implementing a point-of-use (PoU) micronutrient fortification in preschool settings. Preschool children (n = 151) aged 36-79 months were randomized into intervention (n = 76) and control (n = 75) groups, both receiving breakfast maize-porridge with added micronutrient or placebo powder for 52 school days. Process evaluation and early childhood development indicators were used to assess trial feasibility. Process evaluation results showed that the implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Loechl et al (2009) explicitly used programme theory to guide the assessment of the feasibility and acceptability of distributing MNP through a food‐assisted maternal and child health and nutrition programme in Haiti. Ogunlade et al (2011) used an implementation pathway to guide the process evaluation of MNP use in a preschool setting in South Africa, under normal field conditions and implementation constraints. Both studies relied on the use of a theoretical framework to link observed impacts and programme activities, providing useful information for programme replication or scale‐up.…”
Section: Resultsmentioning
confidence: 99%
“…Loechl et al (2009) explicitly used programme theory to guide the assessment of the feasibility and acceptability of distributing MNP through a food‐assisted maternal and child health and nutrition programme in Haiti. Ogunlade et al (2011) used an implementation pathway to guide the process evaluation of MNP use in a preschool setting in South Africa, under normal field conditions and implementation constraints. Both studies relied on the use of a theoretical framework to link observed impacts and programme activities, providing useful information for programme replication or scale‐up.…”
Section: Resultsmentioning
confidence: 99%
“…Both the KDI and the parent rating scale were translated into the local language by an experienced translator who had done this previously for two similar randomised controlled trials [ 38 , 39 ]. Verification of the translation was done during the training of the assessors and corrections where needed were made before final printing of the assessment tools.…”
Section: Methodsmentioning
confidence: 99%
“…The questions in the two assessment tools were translated into the local language (Setswana) by an experienced translator who had previously done this for two similar randomized controlled trials (Ogunlade et al, 2010, Taljaard, Covic, Van Graan, & Jerling, 2013, and was fluent in the language. Validation of the translation was done during training of the assessors and corrections made where necessary, to ensure true meanings were not lost in translation.…”
Section: Psychomotor Milestone Developmentmentioning
confidence: 99%